Experimental diffusion research and assessment of diffusional mobility in HCP Mg–Al-Ga ternary alloys. (September 2022) - Zhou, Zhengfei; Cui, Yu; Wu, Qiaojun; Xu, Guanglong; Zhou, Lian; Cui, Yuwen
Abstract: It is in this work that the diffusion behavior in HCP Mg–Ga binary alloys at temperatures from 673 K to 873 K and in Mg–Al-Ga ternary alloys in 673–723 K was investigated by the solid-state diffusion couple experiments. The inter- and impurity diffusion coefficients were then extracted from the composition profiles acquired by electron probe microanalysis (EPMA) via the Sauer-Freise, Whittle-Green and Hall methods, respectively. The extracted impurity diffusion coefficient of Ga in pure HCP-Mg follows an Arrhenius relation with the pre-exponential factor D 0  = 1.4 × 10 −5  m 2 /s and activation energy Q  = 116869 J/mol. The interdiffusion coefficients of the Mg–Ga binary alloys were found to increase with increasing the Ga content. Whereas in the Mg–Al-Ga ternary, the average main interdiffusion coefficients D ˜ G a G a M g within the investigated composition space is 5.4 times larger than that of D ˜ A l A l M g at 673 K and 4.6 times at 723 K, respectively, revealing that Ga is a much faster diffuser than Al in the ternary alloys. The main interdiffusion coefficients D ˜ G a G a M g and D ˜ A l A l M g, as well as the impurity diffusion coefficients D A l ( M g − G a ) ∗ and D G a ( M g − A l ) ∗ exhibit increasing composition trends as the content of diffusing species increases, either Al or Ga. Close inspection suggests that Ga has significant effect on the diffusion of Al while the Al effect is minor on Ga. The diffusion coefficients extracted in this work, together with other selected diffusion data in literature, were critically evaluated to assess the diffusional mobility for the HCP Mg–Al-Ga ternary alloys. The optimized parameters of diffusional mobilities enable such diffusion behaviors as composition profiles and diffusion paths to be well represented and then predicted, in most cases, consistent with the experimental findings and therefore validating the mobility parameters assessed in this work.